Yemen - Development Policy Review - World Bank (Washington, DC, 2012)
Yemen is the second poorest country in the Middle East and North Africa region, with 42 percent of its population counted as poor in 1998. GDP has stagnated at around US$530 per capita in real terms since 2002. Unemployment, estimated at 11.5 percent in 1999, is expected to have worsened as the population has climbed at 3 percent a year and the labor force has burgeoned. Extreme gender inequalities persist. Malnutrition is so severe that Yemeni children suffer the world's second worst stunting in growth. And natural resources are increasingly constrained. Two-thirds of Yemen's known oil reserves were depleted by 2003, and production has already begun to decline and will plummet by 2012 if no new reserves are discovered. Freshwater is also increasingly scarce: per capita availability in Yemen is about 2 percent of the world average and projected to diminish by a third in the next 20 years because of the expected increase in population. Compounding these economic, social, and resource problems are Yemen's policy and institutional failings, which have prompted donors to cut aid. Yemen received a meager US$13 in development assistance per capita in 2004. In 2005, the Development Assistance Committee cut International Development Association (IDA) 14 (2006-08) allocations to Yemen by nearly a third, and the U.S. government's Millennium Challenge Corporation suspended Yemen's eligibility for assistance because of its worsening corruption, regulatory quality, and fiscal policies. The main challenges to Yemen's growth are the impending rapid decline in oil revenues, the weak capacity of governance institutions, the pressures of high population growth, and the worsening scarcity of freshwater. The country has yet to come to grips with the imminent oil decline and its consequences. The Government is concerned about governance problems and is recently attempting to speed up reforms. The last two challenges-high population growth and water crisis- are long recognized by the government, but reforms have been slow.